Atypical Leber Hereditary Optic Neuropathy: 18 Year Interval Between Eyes. Issue 3 (September 2016) - Ohden, Kaitlyn L.; Tang, Peter H.; Lilley, Chrystia C.; Lee, Michael S.
Abstract : Abstract: A 5-year-old boy developed profound loss of vision in his right eye and was found to have a 11778 mitochondrial point mutation consistent with Leber hereditary optic neuropathy (LHON). He maintained 20/20 vision in the left eye for 18 years until age 23, when he experienced loss of vision in that eye. This 18 year interval between eye involvement in LHON is the longest reported to date and reinforces the variability in presentation and progression seen in this disease.